2018
DOI: 10.5376/jmr.2018.08.0001
|View full text |Cite
|
Sign up to set email alerts
|

Entomological Coinfections of Arboviruses Dengue and Chikungunya Viruses along the Coastline of Kenya

Abstract: Arthropod-borne disease outbreaks as a result of pathogen influx including arboviruses transmitted by strains of Aedes species occur periodically in varying spots in Kenya. However, there has been paucity of documented information on the Aedes species involved in transmission of different haplotypes of arboviruses. This study assessed for concomitant infection of arboviruses in different vectors. Aedes species were sampled by Bio gent sentinel trap. Mosquitoes were stunned at 4°C for 5 minutes; sorted accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Aedes aegypti and A. albopictus of African and Asian origins, respectively, are globally known for their invasive nature and role in transmitting viruses that cause chikungunya, dengue fever, yellow fever, Zika, and encephalitis [32]. The success of these species in virus transmission has been attributed to three mechanisms: interaction of vector and the host, transovarial transmission, and sexual mating [28,33].…”
Section: Overview Of the Main Mosquito Genera Of Public Health Impmentioning
confidence: 99%
See 3 more Smart Citations
“…Aedes aegypti and A. albopictus of African and Asian origins, respectively, are globally known for their invasive nature and role in transmitting viruses that cause chikungunya, dengue fever, yellow fever, Zika, and encephalitis [32]. The success of these species in virus transmission has been attributed to three mechanisms: interaction of vector and the host, transovarial transmission, and sexual mating [28,33].…”
Section: Overview Of the Main Mosquito Genera Of Public Health Impmentioning
confidence: 99%
“…An important species is A. ochraceus which is highly distributed in the arid regions of north-eastern Kenya and linked to the spread of Rift Valley fever virus (RVFV), NDUV, Bunyamwera virus (BUNV), Babanki virus (BBKV), Sindbis virus (SNBV), and Semliki Forest virus (SMFV) in the region [4,11,34,35,36,37,38]. Additionally, this species has also been reported to be associated with RVFV, dengue virus (DENV), and chikungunya virus (CHKV) in coastal counties (Kwale, Kilifi, Mombasa, Lamu) [11,33,39], and some parts of in the western region [22]. Aedes mcintoshi and A. sudanensis are also important arbovirus vectors occasionally reported in coastal and north-eastern regions [4,11,14,22,33,36,40], while A. circumluteolus have been reported in Busia and Garissa counties [4,22,36].…”
Section: Overview Of the Main Mosquito Genera Of Public Health Impmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in Kilosa and the neighbouring Kilombero district have reported a high prevalence of DENV among febrile children seeking health care from hospitals [10,12]. This indicates the possibility of transmission of DENV infection in the ecosystem from mosquito to human and livestock [26-28] hence chance of co-infections in mosquitoes as reported by Ngala [29]. Circulation of DENV has also been recently reported among residents of the neighbouring Kilombero District [12] and elsewhere in Tanzania [9].…”
Section: Discussionmentioning
confidence: 76%